Risk Stratification of Pediatric Patients With Neuroblastoma Using Volumetric Parameters of 18F-FDG and 18F-DOPA PET/CT. (March 2017) - Liu, Chia-Ju; Lu, Meng-Yao; Liu, Yen-Lin; Ko, Chi-Lun; Ko, Kuan-Yin; Tzen, Kai-Yuan; Chang, Hsiu-Hao; Yang, Yung-Li; Jou, Shiann-Tarng; Hsu, Wen-Ming; Yen, Ruoh-Fang
Abstract : Purpose: This study determined the prognostic value of volumetric parameters derived from pretreatment 18 F-FDG and 18 F-DOPA PET/CT of neuroblastoma and their correlation with clinical and histopathologic features. Patients and Methods: A total of 25 children with neuroblastoma underwent pretreatment 18 F-FDG and 18 F-DOPA PET/CT within 4 weeks. The SUVmax of primary tumors on 18 F-FDG and 18 F-DOPA PET were recorded as SUVFDG and SUVDOPA, respectively. For volumetric parameters of primary tumors, 40% of SUVmax was used to generate volume of interest. If the 40% of SUVmax was below 2.5, an SUV threshold of 2.5 was used instead. Metabolic tumor volume (MTV), total lesion glycolysis (TLG), dopaminergic tumor volume (DTV), and total lesion 18 F-DOPA activity (TLDA) were recorded as 18 F-FDG and 18 F-DOPA volumetric parameters. All indices were compared between groups distinguished by survival status and clinical features, including bone marrow involvement, lymph node metastasis, amplification of the MYCN oncogene, invasive features on anatomic images, and risk categories. The Kaplan-Meier method and log-rank test were used to compare the survival curves between groups. Results: The median follow-up period was 28.2 months. Nonsurvivors (20%) tended to have lower SUVDOPA, DTV, and TLDA ( P ⩽ 0.05), and higher SUVFDG, MTV, and TLG (all P < 0.05). Lower 18 F-DOPA uptake is associated with bone marrow and lymph node metastases (all P < 0.05). Higher 18 F-FDG uptake is associated with MYCN amplification (all P < 0.05) and anatomic invasive features of tumors such as vascular encasement or adjacent organ invasion (TLG, P = 0.05). Only volumetric indices (DTV, TLDA, MTV, and TLG) significantly differed among risk groups (all P < 0.05). Conclusions: Pretherapeutic 18 F-DOPA and 18 F-FDG PET provided complementary information, and both can be served for risk stratification. Volumetric indices of 18 F-DOPA and 18 F-FDG PET correlate more highly with risk grouping.